ANALYSIS OF PESTICIDE RESIDUE CONTENT IN RICE IN THE REGION ACEH BESAR DISTRICT - Sofia, sofia; Kartini, Kartini (Jurusan Kesehatan Lingkungan, Poltekkes Kemenkes Aceh, 2022)
The use of pesticides from year to year is increasing. Spraying pesticides on rice can leave residues in the environment and the rice. Pesticide residues are found in soil, water, crops, and harvested commodities. The study aimed to analyze pesticide residues in harvested rice in the district of Aceh Besar. This type of research is descriptive by conducting laboratory examinations using qualitative tests, namely knowing the presence or absence of pesticide residues in rice. The samples were examined using a pesticide test strip G9 fast pesticides detection kit. The research subject is rice from rice that has been sprayed from planting to harvest and taken from farmers in Aceh Besar district. Sampling was done by purposive sampling, taking as many as 30 points in six sub-districts in the district of Aceh Besar. The results of the analysis showed that 29 negative samples contained pesticide residues, there was only 1 positive sample which was indicated by the absence of a blue color change in one of the reagent areas. These results can be influenced by the use of pesticides by farmers who are still below the threshold value, low frequency of spraying, and the influence of rainfall which causes pesticide residues to accumulate with water.It is necessary to carry out repeated analyses of the pesticide content in rice, considering the analysis results are highly dependent on the intensity of pesticide use by farmers and are influenced by the season/rainfall.